Utility of serum galactomannan antigen testing combined with chest computed tomography for early diagnosis of invasive pulmonary aspergillosis in patients with hematological malignancies with febrile neutropenia after antifungal drug treatment - Xiaoning Wang; Guili Guo; Ruibo Cai; Pengcheng He; Mei Zhang (Journal of International Medical Research, 2019)
Objective To investigate the value of serum galactomannan antigen (GM) testing combined with chest computed tomography (CT) as a noninvasive method for early diagnosis of invasive pulmonary aspergillosis (IPA) in patients with hematological malignancies with febrile neutropenia after antifungal drug treatment. Methods We retrospectively analyzed the data of 376 patients with febrile neutropenia from January 2015 to August 2017. All patients were given broad-spectrum antibiotics and divided into the control group (effective antibiotic treatment, no antifungal drugs given) and the observational group (ineffective antibiotic treatment, antifungal drugs given). The serum GM testing, chest CT, and microbiological examination findings were compared between the two groups. Results The false-positive rates of GM testing for IPA in the control and observational groups were 4.04% and 8.65%, respectively, and the false-negative rates in the two groups were 1.10% and 9.62%, respectively. Sixty-five patients in the observational group and 11 in the control group had typical features of CT imaging. Conclusion Clinical weekly screening of serum GM and chest CT may be an effective combined approach to the early diagnosis of IPA in patients with febrile neutropenia, even if they have undergone antifungal treatment.